Cutting a box hedge with a sickle: An intangible cultural heritage - Seiler, Joakim (FormAkademisk, 2023)
United Nations Educational, Scientific and Cultural Organization (UNESCO) has identified craft as an intangible cultural heritage in the Convention for the Safeguarding of the Intangible Cultural Heritage. The nature of this cultural heritage is that it must be practiced by living craftspeople to endure, and when it is performed by very few, it can be seen as endangered. This research, funded by the Carl-Göran Adelswärds Foundation, is a documentation of such a craft: cutting a box hedge with a sickle. At the same time, in this study, a master–apprentice situation was staged in order to safeguard this traditional craft and pass it on to new craftspeople. The core elements of this learning procedure are imitation and feedback. This specific craft is an ancient tradition with very few living practitioners. The garden in which this endangered craft is still practiced is Castello Ruspoli, created in 1611, when sickles where still used for cutting box hedge hedges. Thanks to the restoration and preservation by the current owners, it is one of the most well-preserved gardens from that time. One of the reasons this garden is so special is the way it is cared for by the gardener, Santino Garbuglia, using traditional craft methods that this film article will investigate and show. The author argues that some traditional gardening methods should be considered intangible cultural heritages and safeguarded as such.